2018
DOI: 10.1002/car.2530
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Relationship between Attention‐Deficit/Hyperactivity Disorder and Experiences of Child Maltreatment: A Meta‐Analysis

Abstract: The purpose of this study was to examine the association between attention‐deficit/hyperactivity disorder (ADHD) and experiences of child maltreatment. This study employed several meta‐analyses. Studies included in the meta‐analysis contained a comparison of experiences of child maltreatment in individuals with and without ADHD or assessed the relationship between ADHD symptoms and experiences of child maltreatment. There were 18 studies that met the eligibility criteria. Individuals with ADHD had higher odds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 49 publications
1
15
1
Order By: Relevance
“…Research examining maltreatment and protective services involvement among children with disabilities is hampered by definitional variations concerning both disability and maltreatment (Jones et al 2012 ; Sullivan and Knutson 2000 ), and studies that specifically report on maltreatment among children with neurodisability are negligible. Still, the available evidence indicates that children with certain neurodisabilities (including but not limited to behavioral disorders including autism spectrum disorder and attention deficit hyperactivity disorder, as well as intellectual disability and conduct disorder) are at increased risk of childhood maltreatment and protective services involvement (Maclean et al 2017 ; Lange et al 2013 ; Hibbard and Desch 2007 ; Sullivan and Knutson 1998 ; Clayton et al 2018 ; Burke et al 2011 ; Jones et al 2012 ). For example, a population-based study by Sullivan and Knutson ( 2000 ) found a 31% prevalence rate of maltreatment among children with disabilities (compared to 9% for non-disabled children), with the highest prevalence rates reported for children with behavior disorders, speech/language disorders, and intellectual disability.…”
Section: Introductionmentioning
confidence: 99%
“…Research examining maltreatment and protective services involvement among children with disabilities is hampered by definitional variations concerning both disability and maltreatment (Jones et al 2012 ; Sullivan and Knutson 2000 ), and studies that specifically report on maltreatment among children with neurodisability are negligible. Still, the available evidence indicates that children with certain neurodisabilities (including but not limited to behavioral disorders including autism spectrum disorder and attention deficit hyperactivity disorder, as well as intellectual disability and conduct disorder) are at increased risk of childhood maltreatment and protective services involvement (Maclean et al 2017 ; Lange et al 2013 ; Hibbard and Desch 2007 ; Sullivan and Knutson 1998 ; Clayton et al 2018 ; Burke et al 2011 ; Jones et al 2012 ). For example, a population-based study by Sullivan and Knutson ( 2000 ) found a 31% prevalence rate of maltreatment among children with disabilities (compared to 9% for non-disabled children), with the highest prevalence rates reported for children with behavior disorders, speech/language disorders, and intellectual disability.…”
Section: Introductionmentioning
confidence: 99%
“…The estimated prevalence of childhood maltreatment among college students was 64.7% in China [6]. Research on the short- and long-term consequences of childhood maltreatment suggests that it substantially contributes to child mortality and morbidity, both internalizing and externalizing psychiatric disorders, criminal behaviors, substance use and risky sexual behavior in adolescence and adulthood [5,7,8,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Adverse Childhood Experiences (ACEs) ACEs have been strongly linked to both ADHD and suicide attempts. Childhood physical abuse, sexual abuse, and parental domestic violence are more prevalent among those with ADHD (Clayton, Lee, Cheung, Theule, & Henrikson, 2018;Fuller-Thomson & Lewis, 2015). Similarly, those who have experienced childhood physical abuse, sexual abuse, or parental domestic violence are more likely to attempt suicide in adulthood (Dube et al, 2001;Enns et al, 2006;Fuller-Thomson, Baird, Dhrodia, & Brennenstuhl, 2016).…”
Section: Socioeconomic Status (Ses)mentioning
confidence: 99%